Achieving radiation reduction by adapting to technology advances. Issue 6 (11th May 2021) - Balter, Stephen; Moses, Jeffrey W.
Key Points: This study demonstrates that the combination of image processing enhancements along with meticulous attention by operators to radiation hygiene can lead to significant and clinically meaningful reductions in radiation exposure. The results obtained from a single experienced chronic total occlusion (CTO) operator in two sequential time periods are a reasonable substitute for a randomized trial. Radiation exposure to patients and operators remains a significant hazard of CTO procedures. Avoiding excessive dosage removes a barrier to successful procedural completion.